Pengaruh Rasio Profitabilitas Terhadap Harga Saham: Studi Kasus pada Perusahaan Manufaktur Subsektor Rokok yang Terdaftar di Bursa Efek Indonesia Periode 2014 – 2023 - Pratama Darajat, FIkry; Suria Manda, Gusganda (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The investigation was directed in order to ascertain, analyzing and describing the effect of Return On Assets, Return On Equity and Net Profit Margin on share prices in cigarettes subsector manufacturing companies Listed with the Stock Exchange of Indonesia during 2014-2023. The method used in the study is descriptive verification through a quantitative approach. The sampling technique used in the study is purposive sampling. Obtained 4 out of 5 populations, namely a total of 40 data. The information utilized in this study is supplementary information gleaned from the Indonesian Stock Exchange website and cigarette company websites. The analysis used is the classical assumption test, multiple linear regression analysis, coefficient of determination (R²) test and hypothesis testing. The results of this study state that the coefficient of determination (R²) test obtained a value of 0.794 or 79.4%, then the remaining 0.206 or 20.6% was stated by other factors not examined. Partial test results show that Return On Assets, Return On Equity and Net Profit Margin influence stock prices, and simultaneous test results show that Return On Assets, Return On Equity and Net Profit Margin influence stock prices. Keywords: Return On Asset, Return On Equity, Net Profit Margin, and Stock Prices.